Effect of welding angle variation on impact strength, micro and macrostructural characteristics of SMAW joints in AISI 1020 steel - Aman Aldino; Muhammad Akhlis Rizza; Sugeng Hadi Susilo (Jurnal Polimesin, 2026)
Welding parameters strongly influence the mechanical integrity and metallurgical quality of welded joints. Shielded Metal Arc Welding (SMAW) is valued for its ease of use and versatility across various materials. This study investigates the effect of welding angle variations on the impact strength, microstructure and macrostructure of AISI 1020 steel joints welded using SMAW technique. Welding was performed at angles of 45° and 70° using currents of 80, 90, and 100 A. Charpy impact testing was conducted in accordance with ASTM E23, while macrostructural and microstructural observations were used to evaluate weld quality and the Heat-Affected Zone (HAZ). Impact testing evaluated the internal toughness of the welded joints, while structural observations provided insights into the weld quality and integrity. Results indicated that higher welding currents and larger angles significantly improved impact resistance. The highest impact energy (56 J/cm²) was obtained at 100 A and a 70° welding angle, showing the best impact resilience. The macro and microstructural analysis supported this, with fewer cracks and more evenly distributed martensite, indicating better weld quality.